Frontal sinus augmentation: Preliminary results of a new approach in prosthetic orbital reconstruction. Issue 6 (June 2019) - Toso, Sabine; Nahles, Susanne; Herzog, Michael; Motzkus, Yvonne; Heiland, Max; Raguse, Jan-Dirk
Abstract: Purpose: Reliable application of endosseous implants for prosthetic facial reconstruction depends on the bone volume available at the defect site. Regarding the orbit, sufficient bone presentation in the medial superior orbital rim is limited due to the frontal sinus. The aim of this article is to report for the first time on the augmentation of the frontal sinus for gaining bone volume for supraorbital implant placement. Materials and methods: Between 2007 and 2014, five patients with orbital exenteration were treated by frontal sinus augmentation using autogenous cancellous bone graft from the ilium. Extraoral implants for prosthetic orbit reconstruction were placed 4–7 months later. In advance, cadaver surgery was performed to prove the feasibility of the method. Surgical technique is described, and intraoperative images are provided. Results: The frontal sinus was successfully augmented in all five patients. No major complications related to the procedure were observed. A total of nine orbital implants were inserted in the augmented bone, thereof one sleeping implant. Six implants were restored prosthetically, two implants were lost at exposure. The observation period ranged from 6 to 97 months (mean: 52.8 months). Mean time for patient rehabilitation was 13 months. High patient satisfaction was achieved with the implant-retained orbital prosthesis. Conclusion: The augmentation of the frontal sinus allows implant placement by providing sufficient bone volume in the medial supraorbital rim. Considering the surgical success of this method and patient satisfaction, this new approach is concluded to be a viable option in a unique subset of patients. Highlights: For the first time, augmentation of the frontal sinus is reported. Clinical paper describing this new method for gaining bone volume for supraorbital implant placement. Focus is set on technique and outcome in a selected subset of patients.